2017
DOI: 10.7554/elife.22759
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin activation by LOK phosphorylation involves a PIP2-dependent wedge mechanism

Abstract: How cells specify morphologically distinct plasma membrane domains is poorly understood. Prior work has shown that restriction of microvilli to the apical aspect of epithelial cells requires the localized activation of the membrane-F-actin linking protein ezrin. Using an in vitro system, we now define a multi-step process whereby the kinase LOK specifically phosphorylates ezrin to activate it. Binding of PIP2 to ezrin induces a conformational change permitting the insertion of the LOK C-terminal domain to wedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 43 publications
4
70
0
Order By: Relevance
“…ERM proteins in mammals, Drosophila, and C. elegans, are all critical for the formation of microvilli (Bonilha et al, 1999;Speck et al, 2003;Göbel et al, 2004;Saotome et al, 2004;Karagiosis and Ready, 2004;Bonilha et al, 2006;Casaletto et al, 2011), and C-terminal phosphorylation is thought to be essential for ERM proteins to support microvilli formation (Chen et al, 1995;Kondo et al, 1997;Gautreau et al, 2000;Pelaseyed et al, 2017;Viswanatha et al, 2012). We therefore examined the formation of intestinal microvilli in wild type animals, as well as animals expressing ERM-1[T544A] or ERM-1[T544D], by electron microscopy.…”
Section: T544 Phosphorylation Contributes To Lumen Formation In Tubulmentioning
confidence: 99%
See 1 more Smart Citation
“…ERM proteins in mammals, Drosophila, and C. elegans, are all critical for the formation of microvilli (Bonilha et al, 1999;Speck et al, 2003;Göbel et al, 2004;Saotome et al, 2004;Karagiosis and Ready, 2004;Bonilha et al, 2006;Casaletto et al, 2011), and C-terminal phosphorylation is thought to be essential for ERM proteins to support microvilli formation (Chen et al, 1995;Kondo et al, 1997;Gautreau et al, 2000;Pelaseyed et al, 2017;Viswanatha et al, 2012). We therefore examined the formation of intestinal microvilli in wild type animals, as well as animals expressing ERM-1[T544A] or ERM-1[T544D], by electron microscopy.…”
Section: T544 Phosphorylation Contributes To Lumen Formation In Tubulmentioning
confidence: 99%
“…The transition to a fully open and active conformation involves binding to the plasma membrane lipid phosphatidylinositol-(4,5) bisphosphate (PIP2) as well phosphorylation of a specific C-terminal threonine residue (T567 in ezrin, T564 in radixin and T558 in moesin) (Simons et al, 1998;Nakamura et al, 1999;Barret et al, 2000;Fievet et al, 2004;Coscoy et al, 2002;Yonemura et al, 2002;Hao et al, 2009;Roch et al, 2010). This transition is thought to occur in a multistep process, in which binding to PIP2 induces a partial conformational change that enables binding of a kinase and phosphorylation of the C-terminal threonine (Fievet et al, 2004;Hao et al, 2009;Bosk et al, 2011;Pelaseyed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They found that upon binding to phosphatidylinositol 4,5-bisphosphate (PIP2), ezrin undergoes a conformational change that allows the C-terminal domain of LOK (STK10) to wedge itself between the C-terminal domain and the FERM domain of ezrin, thus activating LOK kinase activity and mediating phosphorylation of the T567 residue of ezrin. As LOK is known to localize to apical membranes, this pathway ensures that dynamic ezrin phosphocycling occurs on the apical side of the cell, thereby maintaining cell polarity (Pelaseyed et al, 2017).…”
Section: Mechanisms Of Cell Polaritymentioning
confidence: 99%
“…The head-to-tail 49 intramolecular interaction between the FERM domain and the C-ERMAD keeps ezrin in a 50 closed configuration where the actin binding site is masked (Bretscher et al, 51 1995). "Opening up" of ezrin requires the FERM domain to bind to PIP2, followed by the 52 phosphorylation of the C-ERMAD (Fievet et al, 2004) (Pelaseyed et al, 2017). So far, the 53 conformations of non-phosphorylated ezrin and of its phosphomimetic mutant have been 54 studied either in solution, with or without PIP2 micelles (Pelaseyed et al, 2017) (Jayasundar 55 et al, 2012), or on bare solid substrates (Liu et al, 2007).…”
mentioning
confidence: 99%
“…"Opening up" of ezrin requires the FERM domain to bind to PIP2, followed by the 52 phosphorylation of the C-ERMAD (Fievet et al, 2004) (Pelaseyed et al, 2017). So far, the 53 conformations of non-phosphorylated ezrin and of its phosphomimetic mutant have been 54 studied either in solution, with or without PIP2 micelles (Pelaseyed et al, 2017) (Jayasundar 55 et al, 2012), or on bare solid substrates (Liu et al, 2007). A recent paper reports a 56 conformational change of the pseudophosphorylated mutant of ezrin upon binding to PIP2-57 containing supported bilayers (Shabardina et al, 2016), but a detailed analysis at high 58 resolution at the nanometer scale of the different membrane-bound conformations of ezrin 59 is still missing.…”
mentioning
confidence: 99%